A Review on Viral Metagenomics in Extreme Environments - Dávila-Ramos, Sonia; Castelán-Sánchez, Hugo G.; Martínez-Ávila, Liliana; Sánchez-Carbente, María del Rayo; Peralta, Raúl; Hernández-Mendoza, Armando; Dobson, Alan D. W.; Gonzalez, Ramón A.; Pastor, Nina; Batista-García, Ramón Alberto (Frontiers in Microbiology, 2019)
Viruses are the most abundant biological entities in the biosphere, and have the ability to infect Bacteria, Archaea and Eukaryotes. The virome is estimated to be at least ten times more abundant than the microbiome with 107 viruses per milliliter and 109 viral particles per gram in marine waters and sediments or soils, respectively. Viruses represent a largely unexplored genetic diversity, having an important role in the genomic plasticity of their hosts. Moreover, they also play a significant role in the dynamics of microbial populations. In recent years, metagenomic approaches have gained increasing popularity in the study of environmental viromes, offering the possibility of extending our knowledge related to both virus diversity and their functional characterization. Extreme environments represent an interesting source of both microbiota and their virome due to their particular physicochemical conditions, such as very high or very low temperatures and >1 atm hydrostatic pressures, among others. Despite the fact that some progress has been made in our understanding of the ecology of the microbiota in these habitats, few metagenomic studies have described the viromes present in extreme ecosystems. Thus, limited advances have been made in our understanding of the virus community structure in extremophilic ecosystems, as well as in their biotechnological potential. In this review, we critically analyse recent progress in metagenomic-based approaches to explore the viromes in extreme environments and we discuss the potential for new discoveries, as well as methodological challenges and perspectives.